PENGARUH UPAH MINIMUM DAN INFLASI TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI JAMBI - Sudirman Sudirman; Lili Andriani (Ekonomis: Journal of Economics and Business, 2017)
Determination of the Minimum wage is based on the necessities of life are worthy(KHL) with attention to productivity and economic growth, while inflation where a situation where price levels are continuously increasing. While the problem of povertyis a classic problem because all countries had a huge poor population. Therefore need to look for a solution to overcome the problem of poverty. This research aims to find out how inflation, the minimum wage can be explained against the poor population in the province of Jambi province Year 2001-2015. This research is quantitative research using time series data). Types of data used in this research is secondary data obtained from the Central Bureau of statistics (BPS) province of Jambi and journals as a supporter. Multiple linear regression analysis of that minimum wages have a negative relationship toward the poor population in the province of Jambi where if the minimum wage goes up 1% then the number of poor population will be down by0.410 and significantly on (a) 5%, and in variables Inflation positive relationship towards the Poor population of Jambi province, if inflation rises 1% then the number ofpoor population will rise of 0.011 and insignificant on a (a) 5%. As for the analysis of the test of the F and t tests can noted that the influence of the free variable (Minimum wage and inflation) against the number of poor population in the province of Jambi simultaneously or together (FR F) effect on the number of poor population. The value of Fhitung and Ftabel (51.194 > 3.89), with significant extent 0.000 < 0.05 then there are significant positive influence. for test t of a variable minimum wage in the get the value of Thitung with the Ttabel of 7.373 > 2.179.Keywords: minimum wage, inflation